The Use Of Animated Video Media To Improve Expository Text Writing Skills Among Grade X Students At SMK Muhammadiyah 4 Kalisat - Fitri Sakinah; Agus Milu Susetyo; Syahrul Mubaroq (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study aims to determine the effectiveness of using animated video-based learning media in improving the expository writing skills of 10th grade students at SMK Muhammadiyah 4 Kalisat. The study used a quantitative approach with a one-group pretest-posttest quasi-experimental design. The research subjects were 10th grade students at SMK Muhammadiyah 4 Kalisat. The research instrument was an expository text writing test administered before and after the experiment. In the pretest stage, students were asked to write expository texts without using animated video media, while in the posttest stage, students wrote expository texts after participating in learning using animated videos that explained the concepts, structure, and linguistic rules of expository texts. Data analysis was performed by comparing the pretest and posttest results. The results showed an increase in students' expository text writing skills after the use of animated video media, especially in terms of grammatical accuracy and text structure completeness. These results indicate that animated video-based learning media are effective as learning media for improving students' expository text writing skills. Thus, the use of animated video media can be an innovative and relevant alternative learning media in Indonesian language learning at the secondary school level.